Transformation of Family Institutions and Redefinition of Gender Roles in the Context of Indonesian Society Modernization ian Urban Society (International Journal of Economics Management and Social Science, 2026)
This study examines the transformation of family institutions and gender role redefinition within Indonesia's modernization context. Utilizing a longitudinal mixed-methods design, the research combines survey data from 926 respondents representing three generations (grandparents, parents, and adult children) with qualitative interviews of 48 families across urban, suburban, and rural areas conducted between February and October 2024. The investigation focuses on changes in family structure, decision-making patterns, domestic labor division, economic provision models, and gender ideology across generations. Findings reveal substantial transformation in family organization, with nuclear family arrangements increasingly dominant (73.2% of younger generation compared to 42.8% of grandparent generation), though extended family networks remain culturally and economically significant. Gender role patterns demonstrate significant but incomplete transformation: while dual-earner arrangements have become normative (68.4% of younger married couples), domestic labor division remains heavily gendered, with women performing 70.3% of household tasks even in dual-earner families. Decision-making has shifted from patriarchal to more egalitarian patterns in younger generations, though significant gender gaps persist in financial and major life decisions. The study identifies three family adaptation models: Traditional Continuity (maintaining conventional gender roles despite modernization pressures), Pragmatic Negotiation (selectively adapting roles based on economic necessity while retaining traditional ideology), and Egalitarian Transformation (fundamentally reorganizing roles based on gender equality principles). These findings illuminate the complex, non-linear nature of gender transformation in transitional societies and highlight persistent structural barriers to gender equality despite ideological shifts.Keywords: Family transformation, gender roles, modernization, work-family balance, Indonesia